Respuesta :
Following BODMAS,
start with the inner brackets first so, 36-5(21/8) + 27 .
Then you multiply: 36 - 105/8 + 27
Work from left to right: answer should be 399/8
Hope this helps :)
Can always check with calculator too XD
Hi. This is not equation as there is no '=' sign I assume you want to simplify this expression.
Use order of operations (PEMDAS).
First thing to do is evaluate the inner parentheses , then the outer.
36-5[(25-4)÷2³]+3³
= 36 - 5 ( 21 / 8) + 3^3
= 36 - 105/8 + 27
= 63 - 13.125
= 49.875 or 49 7/8 Answer